The Paradox of Economic Criminal Law Enforcement After the New Criminal Code Between Regulatory Progressivity and Impunity for Corruption - Guntarwan Indar Wibowo; Suryawan Raharjho; Muh. Syah Quddus (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
Indonesia's persistent corruption problem, characterized by escalating state losses and structural impunity, raises a critical question: does the 2023 Criminal Code reform genuinely strengthen economic criminal law enforcement, or does it merely produce progressive norms without effective implementation? This study aims to analyze the paradox between the regulatory progressivity of the new Criminal Code and the phenomenon of impunity in economic criminal law enforcement in Indonesia. This research employs a normative juridical method, drawing on a conceptual and legislative approach. Data were collected through literature studies involving primary legal materials (laws and regulations), secondary legal materials (academic books and journal articles), and tertiary legal materials (legal dictionaries and institutional reports from KPK, ICW, and PPATK). Analysis was conducted using prescriptive qualitative techniques, including legal interpretation, the construction of legal arguments, and the critical evaluation of norm consistency. The results show that the new Criminal Code strengthens corporate criminal accountability (Article 45), reinforces the fault principle (Article 36), and expands proportional sentencing as a progressive step in addressing modern economic crimes — including corruption that caused state losses reaching IDR 28.4 trillion in 2023 and IDR 310.61 trillion in 2024. However, a paradox persists: these progressive regulations have not translated into effective enforcement due to structural obstacles, including weak inter-institutional coordination among KPK, police, and prosecutors; the complexity of proving cases involving transnational financial networks; and structural impunity driven by perpetrators' political and economic power. The study recommends strengthening inter-institutional coordination and integrating digital technology in cross-jurisdictional investigations, while calling for further empirical and comparative studies to bridge the gap between legal norms and enforcement.